Non-Newtonian coefficient condition for a stable long-time behavior of a single bubble: existence and characteristics of stable solutions - Wolf, Alexandre; Rauh, Cornelia; Delgado, Antonio (Archive of Applied Mechanics, 2020)
The present paper takes up the underlying nonlinear initial value problem from a preceding author’s work about the dynamics of a single bubble in a highly viscous liquid medium under different pressure impacts. The arising ordinary differential equation is mainly based on the constitutive relation of a second-order liquid that in particular includes two non-Newtonian material constants. In this article, the significance of these coefficients is mathematically analyzed in detail by proving the existence of stable solutions of the named initial value problem. This is achieved by special transformations of the differential equation at hand and the introduction of appropriate Lyapunov functions. It particularly turns out that a combined condition of the non-Newtonian coefficients and diverse restrictions to the external pressure impact are decisive for the validity of the existence results. Furthermore, the convergence speed of solutions is investigated by considering the linearized equation associated with the present initial value problem and by applying a special variant of Gronwall’s lemma. The main theoretical result, being the prementioned strong condition for the non-Newtonian coefficients, is finally compared to real data sets.
CRIS-Team Scopus Importer:2020-02-28
Keywords: Bubble dynamics; Gronwall’s lemma; Lyapunov function; Second-order fluid; Stability conditions